Delay Evaluation in Interactive Exchange with Controllable Devices for Some Types of Computer Interfaces - Boole, E.; Stepin, D.; Stepin, V. (Elektronika ir Elektrotechnika, 2008)
In real-time control of devices, connected to the standard computer interfaces, it is essential to evaluate delays in the interactive program exchange with devices. These delays are defined both by the interface type and computer operational environment. The device implementation, registering the delay of program response to events from the device, is presented. These delays can be read and statistically processed in the computer. The presented device and related sample programs in C language support four standard interfaces: RS-232, EPP, USB1 and USB2. The results of the delay evaluation for these interfaces are presented, too. Ill. 4, tabl. 1, bibl. 4 (in English; summaries in English, Russian and Lithuanian).